Telerehabilitation Application In Post Stroke Patients After Hospitalization - Irmina Ika Yuniarti (Journal of Science Innovare, 2023)
Nursing services include promotive, preventive and rehabilitative. Rehabilitation of post-stroke post-hospitalized patients is growing rapidly along with the development of internet use and advances in information technology. Telerehabilitation is an innovation to make it easier for patients to get rehabilitation services as a continuation after treatment at the hospital to improve their motor, speech and psychosocial abilities as a result of a stroke. Telerehabilitation increases the client's comfort in doing exercises during rehabilitation both at home, in the community, health facilities that are easy to reach to help restore the patient's ability to be independent. Several countries have developed telerehabilitation to provide post-hospitalized post-stroke telerehabilitation services considering that there are so many benefits to be gained that it is necessary to consider applying the telerehabilitation system in Indonesia with various adjustments so that it can be implemented optimally.